Teaching numeracy 9 critical habits to ignite mathematical thinking - Pearse, Margie; Walton, K. M. (Kathleen M.) (Corwin Press, 2011)
"Numeracy encompasses deep thinking, meaning making, and sense building; students do not simply do the math, they are taught how to think through the math. Unfortunately, neither numeracy instruction nor numerate thinking are commonly encountered in American mathematics classrooms. We are used to having our students do a problem, and then do more and more of the same type of problem over and over until the is memorized. Students are not encouraged or shown how to think through the math and make sense of it. This book lays a clear and well researched path for any teacher of mathematics to either enhance already strong instruction or revamp lackluster instruction. This book will empower teachers and show them how to fill their mathematics instruction with numeracy"--Publisher.